The antlered ship - Slater, Dashka; Fan Brothers (New York Beach Lane Books, 2017)
An inquisitive fox named Marco and a bored flock of pigeons join the crew of deer Captain Sylvia, setting sail in her antlered ship in search of a wonderful island and finding friendship on the way
1
Keywords: Friendship -- Fiction; Ocean travel -- Fiction; Foxes -- Fiction; Deer -- Fiction; Pigeons -- Fiction; Sea stories